2006
DOI: 10.2139/ssrn.1094834
|View full text |Cite
|
Sign up to set email alerts
|

The Inattentive Participant: Portfolio Trading Behavior in 401(K) Plans

Abstract: Most workers in defined contribution retirement plans are inattentive portfolio managers: only a few engage in any trading at all, and only a tiny minority trades actively. Using a rich new dataset on 1.2 million workers in over 1,500 plans, we find that most 401(k) plan participants are characterized by profound inertia. Almost all participants (80%) initiate no trades, and an additional 11% makes only a single trade, in a two-year period. Even among traders, portfolio turnover rates are one-third the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
94
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 20 publications
15
94
0
Order By: Relevance
“…This is in sharp contrast to findings of studies that observe participant's actual behavior. For example, Agnew, Balduzzi, and Sundén (2003), Mitchell et al (2006) and Ameriks and Zeldes (2004) report that changes in asset allocations are very rare. Our question did not distinguish between changing the allocation of assets and changing the allocation of contributions, so it is possible that participants in our sample referred to changes their contributions.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…This is in sharp contrast to findings of studies that observe participant's actual behavior. For example, Agnew, Balduzzi, and Sundén (2003), Mitchell et al (2006) and Ameriks and Zeldes (2004) report that changes in asset allocations are very rare. Our question did not distinguish between changing the allocation of assets and changing the allocation of contributions, so it is possible that participants in our sample referred to changes their contributions.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…For example, Ameriks and Zeldes (2004) reported that, over a 10-year period, 44% of investors in their sample made no changes to their portfolio allocations, and that an additional 17% of these investors made a single reallocation during this period. Mitchell, Mottola, Utkus, and Yamaguchi (2006) found that, of 1.2 million U.S. employees covered by over 1,500 401(k) investment plans, approximately 80% initiated no trades over a two-year period, while an additional 10% made only a single trade.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…To address this question, we explore factors that influence the efficiency of 401(k) plans, to see whether plan sponsors might enhance plan performance by adding investment choices. Additionally, recent proposals have suggested introducing individually-managed accounts into the U.S. Social Security system (Cogan and 1 For example, Madrian, and Shea (2001) and Choi, Laibson, Madrian, and Metrick (2001) show that automatic enrollment increases 401(k) participation rates and participants tend to stay with the default contribution rate and fund allocation; Ameriks and Zeldes (2004) and Agnew, Balduzzi, and Sunden (2003) document inertia in asset allocations; Mitchell, Mottola, Utkus and Yamaguchi (2006) and Yamaguchi, Mitchell, Mottola, and Utkus (2006) study participant trading behavior and its impact on investment performance in DC plans; Benartzi and Thaler (2001) and Agnew (2002) show evidence of naïve allocation strategy among 401(k) participants; Karlsson, Massa, and Simonov (2007) suggest that investors choose assets as a function of the way they are represented in the menu; Liang and Weisbenner (2002) and Huberman and Sengmueller (2004) study participants investment behavior in company stock. Low financial literacy among 401(k) participants or average households is documented by Hancock (2002) and Lusardi and Mitchell (2007).…”
Section: The Efficiency Of Pension Plan Investment Menus: Investment mentioning
confidence: 99%
“…2 A plan is efficient if its performance cannot be improved at a statistically significant level by adding more investment choices in the plan menu (Elton, Gruber and Blake, 2006). 3 Brown, Liang, and Weisbernner (2007) show that the average number of options in 401(k) plans has increased from fewer than six options in 1993 to 14 options in 2002; Mitchell et al (2006) show the average number of investment options has risen to about 17. Mitchell, 2003).…”
mentioning
confidence: 99%